Enhanced charge generation and transfer performance of the conical bamboo-like TiO2 nanotube arrays photo-electrodes in quantum dot sensitized solar cells. (15th July 2020) - Peng, Zhuoyin; Sun, Zheng; Chen, Jianlin; Li, Wei; Chen, Jian; Liu, Yueli; Chen, Keqiang
Highlights: Conical bamboo-like TiO2 NTs have been prepared by different anodization process. The optical absorption and electron-hole separation property of photo-electrodes have been enhanced. More paths and high rate of charge transfer have been enhanced by the conical bamboo-like TiO2 NTs structure. Conical bamboo-like TiO2 NTs based CuInS2 QDSSCs exhibits photovoltaic efficiency from 4.65% to 5.98%. Abstract: Conical bamboo-like TiO2 nanotubes (NTs) electrodes, instead of the traditional TiO2 NTs and conical TiO2 NTs electrodes, are employed as the photo-electrodes for the fabrication of CuInS2 quantum dot sensitized solar cells (QDSSCs), which have improved deposition content of QDs in solar cells. The distances between each bamboo ring are modulated by the different anodization holding times. In addition, the optical properties of different TiO2 NTs electrodes and CuInS2 quantum dots sensitized photo-electrodes are investigated, which reveals that the deposition content of QDs have been improved by the bamboo rings of conical bamboo-like TiO2 NTs based photo-electrodes to obtain better optical absorption property and charge separation property. More importantly, the bamboo rings in the conical bamboo-like TiO2 NTs structure can provide more paths for the charge transfer, which results in improved charge transfer rate in the QDSSCs. Finally, the optimized conical bamboo-like TiO2 NTs prepared by anodization holding time of 20 min exhibits higher current density, which leads to a significant increasing of the photovoltaic conversion efficiency from 4.65% to 5.98%.